On the Role of Silica Carrier Curvature for the Unloading of Small Drug Molecules: A Molecular Dynamics Simulation Study - Macht, Moritz; Becit, Bahanur; Zahn, Dirk (Journal of Pharmaceutical Sciences, 2020)
We present atomic scale models of differently shaped silica surfaces loaded by gemcitabine and ibuprofene molecules. Despite the dissimilar nature of the drug molecules, their association to silica carriers shows quite similar characteristics. We identify a well-defined contact layer that is stabilized by silica-molecule salt-bridges/hydrogen bonding in parallel to interactions among the drug molecules. Additional loading of the carriers leads to rough films with dynamically evolving asperities rather than layer-by-layer ordering. To elucidate the role of differently shaped silica surfaces, we compared planar slab models and spherical nanoparticles as 2 limiting cases. Despite the strong difference in the curvature of the silica surfaces, our molecular dynamics simulations show only small changes of the unloading characteristics. This suggests that the design of different pore shapes in mesoporous silica–based drug carriers mainly affects the migration kinetics rather than the energetics of drug loading and release.
CRIS-Team Scopus Importer:2020-04-14
Keywords: drug delivery system(s); drug transport; molecular dynamics; molecular modeling; nanoparticle(s)